IMPLEMENTASI MEDIA SMART POP UP BOOK UNTUK MENINGKATKAN LITERASI BACA-TULIS PADA ANAK - Sabitul Kirom; Sri Lestanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Every school must participate in literacy activities, which are required. Through the efforts of the national literacy movement, the government has made this announcement. Literacy activities can be implemented more effectively with the help of interactive learning media. At the moment, children tend to prefer modern media or games like smartphones and tablets. In fact, children's development can be negatively impacted by these various media if they are not closely monitored. As a result, research was conducted on the use of smart pop-up book media in education to familiarize young children with literacy. The reason for this study was to decide the execution of brilliant spring up book media in learning education in youth. Children between the ages of 5 and 6 participated in this study at TK Pertiwi Wonorejo 02 Kec. Talun of the Blitar Empire. A descriptive qualitative research design is used in this study. Based on aspects of children's language literacy development, this study found that smart pop-up book media can help students improve their reading and writing literacy. As a result, it can be concluded that children can improve their reading and writing literacy skills by utilizing smart pop-up book media in early childhood education.